DESIGN AND IMPLEMENTAION OF CLOUD BASED LIGHT INTENSITY MONITORING SYSTEM USING RASPBERRY PI - MR. D. P. BELGAONKAR; MR. S. B. JADHAV (International Journal of Innovations in Engineering Research and Technology, 2021)
Thereare variety of applications for Light Meters for measuring and maintaining adequate light levels such as laboratories, hospitals, schools etc. To maintain healthier and safer environment adequate light levels in the workplace are necessary. Also during summer days, light intensity coming from sun light is too high which has to be controlled for avoiding overheating. This outcomein keeping up light power. Light force estimation should be possible utilizing distinctive sensors. Generally favoured sensors are LDR and photo diode. In the greater part of the applications estimation of light force is important to keep up required measure of light.